Thyroid status and treatment responses of hypothyroid infertile women: a study in a tertiary care hospital of Bangladesh - Aktaruzzaman, A. H. M.; Ahmmed, Afsar; Yasmin, Sabina; Dewan, M. Shafiqul Islam (International Surgery Journal, 2021)
Background: Recently, the prevalence of hypothyroidism in the reproductive age group is found up to 4%. In many studies it had been claimed that, thyroid status is directly involved in women reproductive system. Hypothyroidism can be easily detected by assessing serum thyroid stimulating hormone (TSH) levels. The aim of this study was to dig out the prevalence of hypothyroidism in infertile women and to assess their responses in treatment procedures. Methods: This observational study was conducted National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, Bangladesh during the period from January 2019 to December 2019 in total 236 women of Endocrinology Department treatment. Patients were followed up for six months even if pregnancy was attained. Results: In total 22% (n=52) patients were hypothyroid. Among them 35 (15%) were subclinical hypothyroid and 17 (7%) were frank hypothyroid. Besides these, 73% (n=172) were euthyroid and the rest 5% (n=12) were hyperthyroid. On the other hand, in analysing the outcome (treatment responses) among the hypothyroid subjects we observed regular menstruation, normal ovulation, clinical pregnancy and chemical pregnancy were achieved by 92.31% (n=48), 88.46% (n=46), 50% (n=26) and 69.23% (n=36) subjects respectively. Conclusions: According to the study, the careful diagnosis and treatment of hypothyroidism can ensure benefit a lot rather than going for unnecessary hormone assays and costly invasive procedures in for women of infertility.